Real-world experience with TTFields in glioma patients with emphasis on therapy usage - Jelgersma, Claudius; Alsolivany, Joan; Akkas, Gülsüm; Wasilewski, David; Gastl, Bastian; Misch, Martin; Capper, David; Kaul, David; Bullinger, Lars; Vajkoczy, Peter; Onken, Julia (Frontiers in Oncology, 2025)
Tumor Treating Fields (TTFields) has emerged as a significant adjunctive component in the treatment of high-grade gliomas following the EF-14 trial in 2017. The incorporation of TTFields, alongside cyclic temozolomide therapy, has demonstrated improved patient outcomes when the usage exceeds 18 h per day (75% usage). Post-hoc analysis of the EF-14 trial has demonstrated that therapy usage exceeding 90% is associated with an additional benefit, while rates above 50% have also proven effective in literature. Given the cost-intensive nature and mild- to- moderate constraints associated with the therapy, our objective is to generate real-world data on therapy usage through a retrospective analysis at a high-throughput academic center. Between June 2015 and February 2022, a total of 113 high-grade glioma patients received TTFields therapy. Eight patients discontinued TTFields therapy within 2 months with less than 50% usage and were excluded from further analysis. For the remaining patients, the median age was 51 years (range: 20–76 years) and the mean preoperative Karnofsky index was 80%–90%. Most of the patients (75.2%) initiated therapy concurrently with first-line treatment, of whom 27.6% started TTFields therapy concomitant to the first cycle of temozolomide. 15.2% started TTFields therapy in the second-line and 9.5% in the third-line setting. The study cohort had an average therapy duration of 9.3 months with 3.2 break days per month. The mean therapy usage was 65.5% (SD 17.6%). Usage was highest during the first 3 months, with rates of 77.7%, 72.3%, and 71.6%, and then dropped to around 60% in the following 6 months. Linear regression found no predictors of usage, such as age, timing of therapy initiation, and duration or gender. 55% of patients continued TTFields beyond the first recurrence. Interestingly, no drop in usage rates was observed before tumor recurrence was communicated. However, after diagnosis, patients exhibited a significant drop in usage to an average of 52.3%. This high-volume, real-world TTFields usage data reveal that the extent of usage falls short of the intended 75%. It highlights the importance of monitoring and promoting adherence to maximize its potential benefits in managing high-grade glioma patients. Furthermore, strategies to expedite therapy initiation and improve long-term adherence are warranted.